European Medicines Agency review of ixazomib (Ninlaro) for the treatment of adult patients with multiple myeloma who have received at least one prior therapy. Issue 5 (8th September 2019) - Tzogani, Kyriaki; Florez, Beatriz; Markey, Greg; Caleno, Mariapaola; Olimpieri, Odoardo Maria; Melchiorri, Daniela; Hovgaard, Doris Johanna; Sarac, Sinan Bardakci; Penttilä, Karri; Lapveteläinen, Tuomo; Salmonson, Tomas; Bergh, Jonas; et al.
Abstract : On 21 November 2016, the European Commission issued a marketing authorisation valid throughout the European Union for ixazomib in combination with lenalidomide and dexamethasone for the treatment of adult patients with multiple myeloma who have received at least one prior therapy. Ixazomib was evaluated in one, randomised, double-blind, phase III study comparing ixazomib plus lenalidomide and dexamethasone (n=360; ixazomib arm) versus placebo plus lenalidomide and dexamethasone (n=362; placebo arm) in adult patients with relapsed and/or refractory multiple myeloma who had received at least one prior therapy. The median progression-free survival (PFS) in the intent-to-treat population was 20.6 months in patients treated with ixazomib compared with 14.7 months for patients in the placebo arm (stratified HR=0.742, 95% CI 0.587 to 0.939, stratified p-value=0.012). The most frequently reported adverse reactions (≥20%) within the ixazomib and placebo arms were diarrhoea (42% vs 36%), constipation (34% vs 25%), thrombocytopaenia (28% vs 14%), peripheral neuropathy (28% vs 21%), nausea (26% vs 21%), peripheral oedema (25% vs 18%), vomiting (22% vs 11%) and back pain (21% vs 16%). The scientific review concluded that the gain in PFS of 5.9 months observed with ixazomib was considered clinically meaningful. Concerning the possible uncertainty about the magnitude of the effect, this uncertainty was acceptable given the favourable toxicity profile, and considering that ixazomib is the first agent to allow oral triple combination therapy in this patient population which represents a therapeutic innovation in terms of convenience for patients. Therefore, the benefit–risk for ixazomib in combination with lenalidomide and dexamethasone was considered positive, although the efficacy evidence was not as comprehensive as normally required.